EVALUATION OF THE IMPORTANCE OF SPIRITUALITY AMONG MEDICAL STUDENTS FROM THE 5TH TO 8TH SEMESTER AT UNIEVANGÉLICA AS A MECHANISM FOR MAINTAINING MENTAL HEALTH DURING MEDICAL SCHOOL (CIPEEX, 2025)
The World Health Organization (WHO) recognizes spirituality not merely as a religious practice, but also as a factor that influences quality of life. For medical students, especially during their internship, spirituality proves to be an important resource for psychological balance and mental well-being. This study sought to understand the academic reality of medical students in relation to their emotional state and how spirituality acts in this context. The results indicate that most students show symptoms of anxiety, with less incidence of depression, and that many find spirituality a source of strength to deal with daily difficulties. In addition, caring for others brings greater purpose to their lives, reinforcing their sense of belonging. In summary, spirituality emerges as a valuable tool for these students, helping them cope with stress and providing meaning, comfort, and resilience throughout their academic training.
Keywords: Medical students; Mental health; Spirituality; Socioeconomic profile